Reaction-Induced structural and compositional heterogeneity in amine-cured epoxy/epoxy thermosets: Visualization of heterogeneity using fluorescence lifetime imaging microscopy (FLIM). (24th April 2023) - Woodcock, Jeremiah W.; Stranick, Stephan J.; Kotula, Anthony P.; Chen, Shawn H.; Engmann, Sebastian; Gilman, Jeffrey W.; Holmes, Gale A.
Abstract: The strategic integration of a rhodamine-spirolactam (RS) mechanophore into transparent epoxy-amine (E-A) networks has revealed using fluorescence lifetime imaging microscopy (FLIM), multiple domains in the cured epoxies that are different (compositional and structural heterogeneity) even though only a single glass transition temperature ( T g ) is observed in the solid rheology data. For the E-A networks investigated in this study, the FLIM data suggests that heterogeneity exists at two levels (molecular and macroscopic). Heterogeneity in the network composed of diglycidyl ether of bisphenol-A (DGEBA) epoxy cured with meta-phenylenediamine (m-PDA) is associated with the network being under-cured. In the network composed of the diglycidyl ether of 1, 4-butanediol (DGEBD) cured with m-PDA, heterogeneity is linked to the oligomers that likely self-associate in the 60 mass % DGEBD medium, thereby creating discrete regions of low crosslink density in the cured network. In the DGEBA (80 mass %)/DGEBD (20 mass %) epoxy blend cured with m-PDA, the heterogeneous morphology in this fully cured network is caused by reaction kinetics differences of the two miscible bis-epoxides with m-PDA at the molecular level and the self-association of the oligomers found in the 60 mass % DGEBD medium at the macroscopic level. Graphical abstract: Image 1 Highlights: FLIM imaging of mechanophore enhanced networks provide molecular level and macroscopic level information. Macroscopic heterogeneity in DGEBA/m-PDA Network associated with uneven curing during the network formation process. Macroscopic heterogeneity in DGEBD/m-PDA and DGEBA/DGEBD/m-PDA linked to self-associating oligomers.